P.228 Pre-operative Surrogates Markers of Frailty and Metastatic Spine Disease: Systematic Review. (November 2021) - Touchette, CJ; MacLean, MA; Brunette-Clement, T; Abduljabba, FH; Weber, MH; Fourney, DR
Abstract : Background: Despite the inherent importance of physical reserve and ability to tolerate surgery, pre-operative patient-specific surrogate markers of frailty that may improve accuracy of outcome prognostication following surgery for SMD are not well described. Methods: A systematic review was performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. MEDLINE, Scopus, EMBASE, Cochrane Registry of Controlled Trials, CINAHL, and Web of Science were searched. Quality of evidence was scored using the Oxford CEBM Scoring Tool. Results: Forty studies accounted for 8, 364 patients. Surgical indications included neurological dysfunction, intractable pain, and spinal instability. Tumor histology varied across and within studies. Age, gender, performance status, neurologic function, comorbidities, and biochemical abnormalities were the most frequently analyzed pre-operative surrogate markers of frailty. The most commonly assessed outcomes were overall and progression-free survival; few studies examined health-related quality of life, peri-operative adverse events, and post-operative complications. Conclusions: This study highlights the need for objective measures of frailty in order to improve risk stratification and outcome prognostication among patients receiving surgery for metastatic spinal disease. Future studies should address identified knowledge gaps pertaining to peri-operative adverse events, post-operative complications, and health-related quality of life outcomes.